If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x^2-12x=-4
We move all terms to the left:
2x^2-12x-(-4)=0
We add all the numbers together, and all the variables
2x^2-12x+4=0
a = 2; b = -12; c = +4;
Δ = b2-4ac
Δ = -122-4·2·4
Δ = 112
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{112}=\sqrt{16*7}=\sqrt{16}*\sqrt{7}=4\sqrt{7}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-12)-4\sqrt{7}}{2*2}=\frac{12-4\sqrt{7}}{4} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-12)+4\sqrt{7}}{2*2}=\frac{12+4\sqrt{7}}{4} $
| 5^6x+7=625 | | 45=13x+8 | | 1/2x-20-x=3(2x+1)-2x-1 | | 45=13x8 | | N(0)x=-2 | | 1/2x-20-x=3(2x+11-2x-1 | | 6/7c+3=15 | | W(t)=3t-1;t=-1/3 | | 4x+2=x-13 | | N(-2)=-1-x+4 | | -20=-8-6r | | B(5)x=0 | | W(t)=15t-1 | | z+2/3=6+1/6 | | B(0)x=-2 | | 3/5(2m-10)=2/3m+5.2 | | 6b-3=-27 | | 6b−3=−27 | | W(-1/3)=15t-1, | | X²-3x+11=0 | | 2x-+2=0 | | 4(p-18.97)+2=-2.56 | | 2x+14=6x+38 | | 3x2+10x+3=0 | | x/3=46x | | 2.22=0.4g | | (X+1)^2+(x-2)^2=37 | | W(t)=3t-1t=1/3 | | 2x+1=6x+25 | | F=6.67x10^-11((1x6144)/678.4) | | 10x-5=9+8x | | 3c+5=6(c-3) |